Water Management Challenges in Coastal Polders of Bangladesh: Rethinking Institutional and Policy Issues - Begum, Salma; Huq, Hamidul; Salahuddin, Ahmad; Nelson, Katherine; Amin, Md. Ruhul (2024)
This report documents the results of the study on “Water Management Challenges in Coastal Polders of Bangladesh: Rethinking Institutional and Policy Issues”. The study was carried out to deeper comprehend the role of Water Management Groups (WMGs) and Water Management Associations (WMAs) in the polders in order to plan for a participatory bottom-up approach and propose policy adjustment for comprehensive water management to increase resilience. For effective water management in coastal polders of Bangladesh, the study recommends that the Department of Agricultural Extension (DAE) have the overseeing role of managing Water Management Organizations (WMOs), as it has a strong local presence and a mandate for agricultural development. WMOs members also recommended the same. The focus should be on empowering WMOs by outlining their rights, mandates, and responsibilities, ensuring that they remain central in managing polder operations. Bangladesh Water Development Board (BWDB) should continue providing essential engineering support and submitting rehabilitation requests based on local needs. By strengthening the coordination among stakeholders and placing WMOs at the centre of water management, these measures can ensure long-term sustainability and resilience for Bangladesh’s coastal communities. This study was conducted by the Institute of Development Studies and Sustainability, United International University and International Rice Research Institute, with the support from the CGIAR Initiative on Asian Mega-Deltas.